Neuroinflammation predicts disease progression in progressive supranuclear palsy. Issue 7 (17th March 2021) - Malpetti, Maura; Passamonti, Luca; Jones, Peter Simon; Street, Duncan; Rittman, Timothy; Fryer, Timothy D; Hong, Young T; Vàsquez Rodriguez, Patricia; Bevan-Jones, William Richard; Aigbirhio, Franklin I; O'Brien, John Tiernan; Rowe, James Benedict
Abstract : Introduction: In addition to tau pathology and neuronal loss, neuroinflammation occurs in progressive supranuclear palsy (PSP). However, the prognostic value of the in vivo imaging markers for these processes in PSP remains unclear. We test the primary hypothesis that baseline in vivo imaging assessment of neuroinflammation in subcortical regions predicts clinical progression in patients with PSP. Methods: Seventeen patients with PSP–Richardson's syndrome underwent a baseline multimodal imaging assessment, including [ 11 C]PK11195 positron emission tomography (PET) to index microglial activation, [ 18 F]AV-1451 PET for tau pathology and structural MRI. Disease severity was measured at baseline and serially up to 4 years with the Progressive Supranuclear Palsy Rating Scale (PSPRS) (average interval of 5 months). Regional grey-matter volumes and PET ligand binding potentials were summarised by three principal component analyses (PCAs). A linear mixed-effects model was applied to the longitudinal PSPRS scores. Single-modality imaging predictors were regressed against the individuals' estimated rate of progression to identify the prognostic value of baseline imaging markers. Results: PCA components reflecting neuroinflammation and tau burden in the brainstem and cerebellum correlated with the subsequent annual rate of change in the PSPRS. PCA-derived PET markers of neuroinflammation and tau pathology correlated with regional brain volume in the same regions. However, MRI volumes alone did not predict the rate of clinical progression. Conclusions: Molecular imaging with PET for microglial activation and tau pathology can predict clinical progression in PSP. These data encourage the evaluation of immunomodulatory approaches to disease-modifying therapies in PSP and the potential for PET to stratify patients in early phase clinical trials.